Adiposity and risks of vascular and non-vascular mortality among Chinese adults with type 2 diabetes: a 10-year prospective study. Issue 1 (18th January 2022) - Iona, Andri; Bragg, Fiona; Guo, Yu; Yang, Ling; Chen, Yiping; Pei, Pei; Lv, Jun; Yu, Canqing; Wang, Xiaohuan; Zhou, Jinyi; Chen, Junshi; Clarke, Robert; et al.
Abstract : Introduction: Among individuals with diabetes, high adiposity has been associated with lower cardiovascular disease (CVD) mortality (the so-called 'obesity paradox' phenomenon) in Western populations, for reasons that are still not fully elucidated. Moreover, little is known about such phenomena in Chinese adults with diabetes among whom very few were obese. We aimed to assess the associations of adiposity with vascular and non-vascular mortality among individuals with diabetes, and compare these with associations among individuals without diabetes. Research design and methods: In 2004–2008, the prospective China Kadoorie Biobank recruited >512 000 adults from 10 areas in China. After 10 years of follow-up, 3509 deaths (1431 from CVD) were recorded among 23 842 individuals with diabetes but without prior major diseases at baseline. Cox regression yielded adjusted HRs associating adiposity with mortality. Results: Among people with diabetes, body mass index (BMI) (mean 25.0 kg/m 2 ) was positively log linearly associated with CVD incidence (n=9943; HR=1.19 (95% CI 1.15 to 1.22) per 5 kg/m 2 ), but showed U-shaped associations with CVD and overall mortality, with lowest risk at 22.5–24.9 kg/m 2 . At lower BMI, risk of death (n=671) within 28 days of CVD onset was particularly elevated, with an HR of 3.26 (95% CI 2.29 to 4.65) at <18.5 kg/m 2 relative to 22.5–24.9 kg/m 2, but no higher mortality risk at BMI ≥25.0 kg/m 2 . These associations were similar in self-reported and screen-detected diabetes, and persisted after extensive attempts to address reverse causality and confounding. Among individuals without diabetes (mean BMI 23.6 kg/m 2 ; n=23 305 deaths), there were less extreme excess mortality risks at low BMI. Conclusions: Among relatively lean Chinese adults with diabetes, there were contrasting associations of adiposity with CVD incidence and with mortality. The high mortality risk at low and high BMI levels highlights, if causal, the importance of maintaining normal weight among people with diabetes.